Iodine Content of Salt Use after Years of Universal Iodization Policy and Knowledge on Iodized Salt among Households in the Sissala East Municipality in Upper West Region of Ghana - Prince Kubi Appiah; Clement Tiimim Yanbom; Martin Amogre Ayanore; Alex Bapula (Journal of Food Quality)
Background. Iodine deficiency is a global public health concern as it leads to inadequate production of thyroid hormone in the body, causing too many destructive consequences on the roles and functions of different human organs and muscles including brain growth and can manifest into many damaging effects such as intestinal cerebral impedance, cancer of intestine, breast disorders, and physical deformities like goitre and cretinism to one’s body. Despite all these negative effects, there are several important public health programs including universal salt iodization (USI) to improve on households’ iodine intake, notwithstanding this, countless families are still eating foods containing less iodine or no iodine at all. Hence, this study examined the intake of iodized salt after years of universal salt iodization and the knowledge on iodized salt among households in the Sissala East Municipality. Method. A descriptive cross-sectional study was adopted to collect data for the study. Data were collected from women in charge of household meal preparation using a semistructured questionnaire and rapid field iodine test kits. The Statistical Package for Social Sciences (SPSS) version 20 was used for the data analysis and presented in tables and graphs. p value <0.05 was considered as statistically significant. Findings. Only 41.4% of the households have good knowledge on benefits of iodized salt and dangers associated with iodine deficiency. It was realized that the health workers (46.6%) and television were the main sources of information on iodized salt. Household salt usage with adequate (>15 ppm) levels of iodine was 44.0%; however 85.9% of the salts were stored in covered containers. The study showed significant associations between knowledge on iodized salt and educational level (p≤0.001), occupation (p=0.043), religion (p=0.027), and ethnic lineage (p=0.046). Also, the use of iodized salt showed associations with the educational level (p≤0.001), occupation (p=0.003), religion (p=0.042), and knowledge on iodized salt (p≤0.001). Conclusions. Only about 4 in 10 households were consuming salt with adequate iodine, and this coverage is very low compared with the 90% or more coverage recommended by WHO/UNICEF/ICCIDD. Having secondary and tertiary education and having good knowledge of iodized salt has a great influence on the use of iodized salt; however, with this low level of knowledge of importance of iodized salt among women responsible for house food preparations, there is the need for health professionals to intensify education and promotion on iodized salt in the area and to monitor and verify iodine content of salts produced and sold in the market all times, as the source of the salt might have contributed to the low levels of iodine in the household salt.